ChemInform Abstract: Synthesis of Isoxazoline Derivatives Based on Nitrile Oxide Cycloaddition of Nitroso‐Nitro‐Enamine. Issue 10 (February 2016) - Kondacs, Laszlo Andras; Pilipecz, Mihaly Viktor; Mucsi, Zoltan; Balazs, Barbara; Gati, Tamas; Nyerges, Miklos; Dancso, Andras; Nemes, Peter
Abstract: Substrate (I) reacts with a broad spectrum of unsaturated dipolarophiles to produce novel isoxazolyl‐pyrroline structures in generally low to moderate yields.